Efek Modal Sosial Informal terhadap Efisiensi Pasar Lokal Perdesaan dalam Ekonomi Rural Kontemporer - M. Alhudhori (Jurnal Ilmiah Universitas Batanghari Jambi, 2026)
This study analyzes the role of informal social capital in shaping the efficiency of local rural markets in Indonesia. Using a qualitative approach based on institutional economics and economic sociology, the research shows that trust, customary norms, and informal social networks function as alternative institutions that lower transaction costs and support market stability. However, informal social capital is also ambivalent because it operates within customary structures and unequal gender relations, creating economic exclusion, particularly for women. These findings confirm that rural market efficiency is contextual and social, and requires a sensitive integration of informal institutions and formal market mechanisms.